Advances in 3D-printed ultraviolet light responsive hydrogels in drug release - A mini review - Fatin Ayu Kartika, Mohd Suzaki; Norazlianie, Sazali; Afdhal, Junaidi; Mimi Sakinah, Abdul Munaim; Noor Azizah, Sidek; Wan Norharyati, Wan Salleh; Norsuhailizah, Sazali (Penerbit UMP, 2025)
This review digs into how ultraviolet (UV) light-responsive hydrogels, paired with cutting-edge 3D and 4D printing, enable personalized drug delivery. These hydrogels canabsorbUV light and shift the structure, so that the hydrogels can release the drugstraight to the target site.Photochromic compounds like azobenzene, spiropyran, and spirooxazinegive the function of absorbing UV light to activate the release mechanism of the drugs to the target area. These molecules flip back and forth in response to UV light, letting the hydrogel swell, change its pores, and control the movement of drugs through it. Basically, the hydrogel becomes a programmable carrier. By using3D and 4D printing, these hydrogels can be built with variousprecision, containingtiny channels, built-in drug reservoirs, and complex, layered shapes.The review lines up UV-responsive hydrogels against traditional drug delivery systems and shows how these hydrogelsare better at releasing drugs on demand, limiting exposure to the rest of the body, and cutting down on side effects. To understand on how these hydrogels work, the review also discussing a fewtestsofthehydrogels: FTIR, UV-Vis spectroscopy, SEM, and rheology. These tests show whether the hydrogels hold up physically, stay chemically stable, and actually respond to UV light according to the wavelength and area of the hydrogel exposed to the UV light.As for the disadvantages affected thehydrogels performance towards manufacturing process—cost, environmental impact, how to scale up production, and whether these materials stay safe in the bodyfor along term. The review looks at how researchers are tackling these problems, fromsuggestion of the materials themselves, to mixing in hybrid polymers, to adding nanoparticles for extra responsiveness.The paper points to new frontiers: hydrogels that respond to visible or near-infrared light, platforms that respond to more than one trigger, and smart 4D-printed patches that adapt to patients in real time.Overall, UV-responsive, 3D-printed hydrogels are shaping up to be a big leap forward for safer, smarter, and more sustainable healthcare